Some new and known species of Dorylaimoidea (Dorylaimida: Nematoda) from Natural forest of Arunachal Pradesh, India (Journal of Nematode Morphology and Systematics, 2010)
Three new and eleven known species of dorylaim nematodes belonging to the families Aporcelaimidae, Qudsianematidae and Nordiidae are described and reported from natural forests of Arunachal Pradesh, India. Aporcelaimellus rotundicaudatus sp. n. is characterised by having body 1.6-1.8 mm long, lip region offset, odontostyle 18-19 μm long with aperture about three-fi fths of its length, transverse vulva, vagina without pars refringens, short conoid to hemispheroid tail, and males with dorylaimoid spicules and 4-5 ventromedian supplements. Labronema enigmatum sp. n. is characterized by its body 2.1-2.5 mm long, lip region well offset by constriction, odontostyle slender and 31-32 μm lon, ‘double’ guiding ring; transverse vulva, Z-organ in the uterus, short bluntly rounded to conoid tail, and males with 18 spaced ventromedian supplements and prerectum extending beyond the range of supplements. Oriverutus neopagarus sp. n. is characterized by having body 0.81-1.02 mm long, lip region offset by constriction, lips lobe-like with raised labial papillae, odontostyle slender and 16.0-18.5 μm long, short conoid cardia with cardiac disc, cardiac glands absent, elongate-conoid tail with slightly dorsally bent tip, and males with 4-6 spaced ventromedian supplements. The rare nematode species Mitoaxonchium basalticum is described for the fi rst time from India. Labronema nepalense, Makatinus heynsi, Paraxonchium parvus, Aporcelaimellus chauhani, Thonus goaensis, Labronemella loofi , Discolaimus texanus, Acephalodorylaimus attenuatus, Oriverutus longistylus and Oriverutus asaccatus are reported for the fi rst time from Arunachal Pradesh.